Analisis Penerapan Manajemen Risiko yang Terstruktur dan Komprehensif di PT. XYZ Sebagai Perusahaan Asuransi - Masadjie Masadjie; Franciskus Antonius (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the implementation of risk management at PT XYZ, a company engaged in the field of guarantee agency services. Methodologically, this study was designed as a qualitative descriptive study with primary data collected through in-depth interviews. The results of the analysis indicate that PT XYZ has successfully implemented a risk management system that meets two main criteria: comprehensive in scope and structured in its framework. This structured implementation is realized through a collaborative risk identification process, involving various work units within a systematic framework. The comprehensive aspect is reflected in the risk assessment approach that combines qualitative considerations to obtain a complete and comprehensive picture of the risk. This combination ensures that all dimensions of risk, both quantifiable and strategic and reputational, are well mapped. The study revealed that the mitigation and monitoring measures implemented by the company are sustainable, further emphasizing the systemic and structured nature of the entire risk management process. This implementation has gone beyond the basic objective of merely meeting regulatory compliance. The system has evolved into a strategic enabler that actively supports strategic decision-making, maintains the company's reputation, and ultimately ensures business sustainability in the face of a dynamic risk landscape. These findings demonstrate that a structured and comprehensive risk management framework is not an administrative burden, but rather a strategic investment for long-term business resilience and growth.